Effect of electron-beam irradation on pik melting temperature of polymer blends - Żenkiewicz, M.; Kurcok, M. (Polimery, 2022)
The effects of the electron radiation dose and presence of a compatibilizer on the peak melting temperature (Tpm) of the crystalline phase, of granulated polymer blends were studied. The samples were prepared from basic polymer blend composed of low-density polyethylene (PE-LD), high-density polyethylene (PE-HD), polypropylene (PP), polystyrene (PS), and poly(ethylene terephthalate) (PET). As the compatibilizers, the styrene-ethylene/butylene-styrene elastomer grafted with maleic anhydride (SEBS-g-MA) or trimethylol propane trimethylacrylate (TMPTA) were used. It was found that addition of compatibilizer irrespective of its type and amount had no significant effect on Tpm. Decrease in the Tpm value with increase in the electron radiation dose for the crystalline phase of PE-LD, PE-HD, and PP was observed.